Identifying and controlling metabolic skin disorders - Adams, E. S. (The Physician and Sportsmedicine, 2004)
Inflammatory skin conditions can present obstacles that affect athletic participation. In eczema and psoriasis, cutaneous lesions can lead to skin breakdown, which may disqualify an athlete from participation and may also contribute to secondary infection. Adequate control of chronic skin conditions can, therefore, ensure more consistent athletic participation, and successful treatment may improve social functioning, as well. Clinicians treating athletes who have exercise-induced urticaria should be aware of the need for close observation and continual reassessment to distinguish between cholinergic urticaria and exercise-induced anaphylaxis.